Biodegradation of fenoxaprop-P-ethyl (FE) by Acinetobacter sp. strain DL-2 and cloning of FE hydrolase gene afeH. (June 2015) - Dong, Weiliang; Jiang, Sheng; Shi, Kaiwen; Wang, Fei; Li, Shuhuan; Zhou, Jie; Huang, Fei; Wang, Yicheng; Zheng, Yuxiao; Hou, Ying; Huang, Yan; Cui, Zhongli
Highlights: A metabolite of FE by strain DL-2 was first identified by HPLC–MS. The novel FE esterase gene AfeH was first cloned from Acinetobacter sp. The recombinant enzyme AfeH was expressed, purified and characterized. AfeH had better activity for different p -nitrophenyl esters. Abstract: Fenoxaprop- P -ethyl (FE) is widely used as a post-emergence aryloxyphenoxy propionate (AOPP) herbicide in agriculture. An efficient FE-degrading strain DL-2 was isolated from the enrichment culture and identified as Acinetobacter sp. and the metabolite fenoxaprop acid (FA) was identified by HPLC/MS analysis. The strain DL-2 could also degrade a wide range of other AOPP herbicides. A novel FE hydrolase esterase gene afeH was cloned from strain DL-2 and functionally expressed in Escherichia coli BL21(DE3). The specific activities of recombinant AfeH was 216.39 U mg −1 for FE with K m and V max values of 0.82  μ M and 7.94  μ mol min −1  mg −1 . AfeH could also hydrolyze various AOPP herbicides, p -nitrophenyl esters and triglycerides. The optimal pH and temperature for recombinant AfeH were 9.0 and 50 °C, respectively; the enzyme was activated by Co 2+ and inhibited by Ca 2+, Zn 2+, Ba 2+ . AfeH was inhibited strongly by phenylmethylsulfonyl and SDS and weakly by dimethyl sulfoxide.